The Venus secret. Creativity as a process of the conscious and subconscious in Barrística Art in clay - Cabeça, Paulo (2021)
This work aims to demonstrate the phenomenon of artistic creativity in Barrística (Art in clay) as a process of the conscious and subconscious. To this end we will analyze this Art from its manifestations in the Paleolithic to the present day, through the Primitive Art, Machado de Castro sculpture productions, Barcelos crafts, World Heritage Estremoz figurines, Art Brut and the Aldeia da Terra project. Why did the paleolithic man elaborate so many “Venus” female figures in stone, bone and clay? What is the secret of the Paleolithic Venus?